(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2026)
The development of e-government has encouraged local governments to improve public services through digital platforms. However, Bunaken District, Manado City, faced challenges in delivering public information and administrative services due to the lack of a dedicated website and limited digital competencies among its staff. This community service program aimed to enhance the capacity of district personnel in developing and managing a website to support administrative functions, transparency, and public service delivery. The program was implemented through four stages: needs assessment and planning, website development training workshops, continuous mentoring, and post-training evaluation. The training focused on website design, content management systems (CMS), digital content management, and website maintenance. The results indicated a significant improvement in participants’ information and communication technology (ICT) skills, particularly in website management and content updating. Furthermore, an operational district website was successfully developed and utilized as a medium for disseminating public information and supporting administrative services. The implementation of the website contributed to improved transparency, accessibility of information, and digital public services. In conclusion, website development training and mentoring effectively strengthened the digital administrative capacity of Bunaken District and supported the implementation of e-government at the local government level. Continuous technical assistance and periodic capacity-building programs are recommended to ensure the sustainability of website management and development.